Protective role of Moringa oleifera leaves extract against zinc oxide nanoparticles induced oxidative stress and infertility in adult male rats - Mohammed, Hemn Anwar; Mohammed, Sulaf Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Nowadays, zinc oxide nanoparticles (ZnO-NP) are one of the most commonly used nanoparticles. They are utilized in different fields, such as agriculture, industry, and biomedicine, and their release into the environment has a negative impact on humans. Moringa oleifera is a medicinal plant with a high nutritional value and a potential antioxidant property. Despite this, research on the impact of M. oleifera on the male reproductive system has been limited. Aim: The aim of the present study was to evaluate the ameliorative role of Moringa oleifera leaf extract on ZnO-NP induced oxidative stress and testicular toxicity. Materials and methods: zinc oxide nanoparticles were synthesized by the sol-gel approach and characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and energy dispersive spectroscopy (EDS). Moringa oleifera leaves were extracted by the maceration method. Thirty-six adult male albino rats were randomly divided into six experimental groups (n = 6), Group (I) control received 1ml/day of 1% dimethyl sulfoxide (DMSO) as a vehicle for 4 weeks and 0.5 ml normal saline injected intraperitonially once a week for 2 weeks, group (II) and group (III) received an extract of M. oleifera leaves by oral gavage at a dosage of 400 and 600 mg/kg.bw/day respectively for 4 weeks, group (IV) received 150 mg/kg.bw ZnO-NP injected intraperitonially once a week for 2 weeks, group (V) and group (VI) received 150 mg/kg.bw ZnO-NP injected intraperitonially once a week for 2 weeks co-administrated with an extract of M. oleifera leaves at a dosage of 400 and 600 mg/kg.bw/day respectively for 4 weeks. At the end of the experiment, the rats were sacrificed, and blood samples were collected for estimation the level of serum testosterone. The epididymis was used for semen collection and analysis. The testes were dissected out from each rat and homogenized for the measurement of oxidative stress biomarkers. Results: The levels of serum testosterone, sperm count, normal sperm morphology, testicular weight, catalase, and glutathione peroxidase were significantly decreased (p<0.01) in the ZnO NP-treated group. While the level of Malondialdehyde (MDA), and abnormal morphology were significantly increased (p<0.0001) in the ZnO-NP treated group. M. oleifera leaf extract caused significant increase (p<0.01) in the levels of testosterone, sperm count, normal morphology, and catalase, and significantly reduced (p<0.01) Malondialdehyde (MDA) levels and abnormal morphology in a dose-dependent manner in the groups (II) and (III) compared to the control group (I). ZnO-NP co-administrated with an extract of M. oleifera leaves of groups (V) and (VI) extract significantly increased (p<0.01) the levels of testosterone, sperm count, normal morphology, testicular weight, catalase, and glutathione peroxidase, and, significantly reduced (p<0.01) MDA and abnormal morphology in a dose-dependent manner when compared with the ZnO-NP treated group. Conclusion: ZnO-NP caused oxidative stress in the rats, while the oral administration of Moringa oleifera leaf extract significantly mitigated the testicular toxicity induced by ZnO-NP in a dose-dependent manner.
Keywords: Zinc oxide nanoparticle; sperm count; spermatogenesis; oxidative stress; MDA; testicular toxicity; antioxidant; catalase; moringa oleifera; Extraction; XRD; FESEM